Failure tolerance of the human lumbar spine in dynamic combined compression and flexion loading. (April 2022) - Tushak, Sophia K.; Paul Donlon, John; Gepner, Bronislaw D.; Chebbi, Aida; Pipkorn, Bengt; Hallman, Jason J.; Forman, Jason L.; Kerrigan, Jason R.
Abstract: Vehicle safety systems have substantially decreased motor vehicle crash-related injuries and fatalities, but injuries to the lumbar spine still have been reported. Experimental and computational analyses of upright and, particularly, reclined occupants in frontal crashes have shown that the lumbar spine can be subjected to simultaneous and out-of-phase combined axial compression and flexion loading. Lumbar spine failure tolerance in combined compression-flexion has not been widely explored in the literature. Therefore, the goal of this study was to measure the failure tolerance of the lumbar spine in combined compression and flexion. Forty lumbar spine segments with three vertebrae (one unconstrained) and two intervertebral discs (both unconstrained) were pre-loaded with axial compression (2200N, 3300N, or 4500N) and then subjected to rotation-controlled dynamic flexion bending until failure. Clinically relevant middle vertebra fractures were observed in twenty-one of the specimens, including compression and burst fractures. The remaining nineteen specimens experienced failure at the potting-grip interface. Failure tolerance varied within the sample and were categorized by the appropriate data censoring, with clinically relevant middle vertebrae fractures characterized as uncensored or left-censored and potting-grip fractures characterized as right-censored. Average failure force and moment were 3290N (range: 1580N to 5042N) and 51Nm (range: 0Nm to 156 Nm) for uncensored data, 3686N (range: 3145N to 4112N) and 0Nm for left-censored data, and 3470N (range: 2138N to 5062N) and 101Nm (range: 27Nm to 182Nm) for right-censored data. These data can be used to develop and improve injury prediction tools for lumbar spine fractures and further research in future safety systems.